Genetic Diversity among Flue-cured Tobacco Cultivars Based on RAPD and AFLP Markers - Han Yao Zhang; Xiao Zhen Liu; Chuan Sheng He; Yu Ming Yang (Brazilian Archives of Biology and Technology, 2008)
The aim of this work was to study the genetic diversity among flue-cured tobacco cultivars. RAPD and AFLP analyses were used to assess the genetic similarity among selected accessions of flue-cured tobacco. Seventy eight RAPD and 154 AFLP polymorphic bands were obtained and used to assess the genetic diversity among 28 tobacco accessions. The cultivar relationships were estimated through the cluster analysis (UPGMA) based on RAPD data and AFLP data. The accessions were grouped into three major clusters and these shared common ancestry clustered together.